Emerging therapeutic strategies in hypoxic-ischemic encephalopathy: a focus on cognitive outcomes - Marques, Kethely L.; Rodrigues, Victor; Balduci, Cassiana T. N.; Montes, Guilherme C.; Barradas, Penha C.; Cunha-Rodrigues, Marta C. (Frontiers in Pharmacology, 2024)
Perinatal hypoxia-ischemia represents a significant risk to CNS development, leading to high mortality rates, diverse damages, and persistent neurological deficits. Despite advances in neonatal medicine in recent decades, the incidence of HIE remains substantial. Motor deficits can manifest early, while cognitive impairments may be diagnosed later, emphasizing the need for extended follow-up. This review aims to explore potential candidates for therapeutic interventions for hypoxic-ischemic encephalopathy (HIE), with a focus on cognitive deficits. We searched randomized clinical trials (RCT) that tested drug treatments for HIE and evaluated cognitive outcomes. The results included studies on erythropoietin, melatonin, magnesium sulfate, topiramate, and a combination of vitamin C and ibuprofen. Although there are several indications of the efficacy of these drugs among animal models, considering neuroprotective properties, the RCTs failed to provide complete effectiveness in the context of cognitive impairments derived from HIE. More robust RCTs are still needed to advance our knowledge and to establish standardized treatments for HIE.